2013
DOI: 10.1007/s00268-013-2243-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of Surgery in Low‐ and Middle‐income Countries: A Systematic Review

Abstract: Simple surgical interventions that are life-saving and disability-preventing should be considered as part of public health policy in LMIC. We recommend an investment in surgical care and its integration with other public health measures at the district hospital level, rather than investment in single disease strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
168
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 213 publications
(174 citation statements)
references
References 53 publications
1
168
0
5
Order By: Relevance
“…The additive morbidity and mortality associated with emergency surgery diminishes its cost-and clinically-effective, particularly for inguinal hernias presenting with obstruction or strangulation. [14,24,31,32] Lastly, these findings demonstrate that inguinal hernias left untreated are associated with significant disability. Hernias result in disability due to embarrassment, pain and limitation of activities.…”
Section: Discussionmentioning
confidence: 90%
“…The additive morbidity and mortality associated with emergency surgery diminishes its cost-and clinically-effective, particularly for inguinal hernias presenting with obstruction or strangulation. [14,24,31,32] Lastly, these findings demonstrate that inguinal hernias left untreated are associated with significant disability. Hernias result in disability due to embarrassment, pain and limitation of activities.…”
Section: Discussionmentioning
confidence: 90%
“…Many of these injuries are surgically treatable, yet a widespread perception persists that surgery is inordinately expensive presents a major barrier to & Erik J. Kramer erik.kramer@yale.edu the implementation of surgery in the global health agenda [2,3]. However, recent studies have demonstrated strong evidence that surgery, including orthopaedic intervention, is often as cost-effective as many non-surgical interventions in widespread use in LMICs [4][5][6][7]. Musculoskeletal injuries contributed heavily to this growing burden as a result of the proliferation of access to motorized transportation and corresponding increases in morbidity and mortality in LMICs [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The first major concern is cost. 11 Although the cost of a new RVM is approximately $5,000, Respiratory Motion has permanently donated 2 monitors to the Kijabe Hospital under their global outreach program to improve patient care and education. The philanthropic mission is to improve patient care and practitioner education in the peri-intubation period and decrease the need for other expensive and invasive testing, such as arterial blood gas measurement.…”
Section: Discussionmentioning
confidence: 99%